Paranormal Believers' Susceptibility to Confirmatory Versus Disconfirmatory Conjunctions. Issue 4 (25th April 2016) - Rogers, Paul; Fisk, John E.; Lowrie, Emma
Summary: This study examines paranormal believers' susceptibility to the conjunction fallacy for confirmatory versus non‐confirmatory conjunctive events. Members of the UK public (N = 207) read 16 hypothetical vignettes before judging the likelihood that each constituent and their conjunction would (co) occur. Event type (paranormal versus non‐paranormal), outcome type (confirming versus disconfirming) and level of paranormal belief (in either extrasensory perception, psychokinesis or life after death)—plus relevant interaction terms—were entered into a linear mixed model analysis. As hypothesised, paranormal belief was associated with more conjunction errors regardless of event type with, in general, more errors made for confirmatory over disconfirmatory conjunctions. These trends existed for extrasensory perception and psychokinesis believers with those for life after death believers approaching significance. Consistent with Crupi and Tentori's Confirmation–Theoretical Framework, current findings suggest that paranormal believers are prone to a generic and confirmatory conjunction fallacy. Theoretical implications, methodological limitations and future research ideas are discussed. Copyright © 2016 John Wiley & Sons, Ltd.